BIOECOLOGY AND SIGNIFICANCE OF CATNIP (NEPETA CATARIA L.) IN THE KHOREZM REGION - Odilbekovich, Jumaniyozov Jalolbek; kizi, Omanbayeva Kumush Mukhtor (American Journal of Biology and Natural Sciences, 2025)
This article provides scientific information about the morphological structure, distribution areas, chemical composition, and medicinal significance of the plant Nepeta cataria L. (catnip) in the Khorezm region. Additionally, the cultivation technology of this plant is discussed. The plant is known for its sedative, diaphoretic, and antitussive effects. The research highlights the importance of catnip in traditional medicine and the pharmaceutical industry, as well as its environmental and cultivation benefits. This study also explores its potential uses in aromatherapy, food, and beverages, and offers insights into its ecological adaptability.